Insecticide resistance mutations of Anopheles species in the Republic of Korea. - Jiseung Jeon; Heung Chul Kim; Terry A Klein; Hojong Jun; Kwang Shik Choi (PLoS Neglected Tropical Diseases)
The number of reported malaria cases transmitted by Anopheles mosquitoes in the Republic of Korea (ROK) increased from 420 in 2022 to 746 in 2023, a 77.6% increase. Eight Anopheles species are currently reported in the ROK, including six species belonging to the Anopheles Hyrcanus Group and one species each belonging to the Barbirostris Group and Lindesayi Group. However, studies on insecticide resistance in the ROK has predominantly concentrated on Anopheles sinensis or more broadly, members of the Hyrcanus Group. Reported differences in vector competence and ecological characteristics of mosquito species in the ROK highlight the importance for conducting accurate evaluations of insecticide resistance for each of the Anopheles species for informing the potential efficacy of vector control to reduce malaria transmission. All eight species of Anopheles mosquitoes were collected in/near the demilitarized zone (DMZ), a malaria high-risk region in the ROK. Additional specimens were collected in Seoul [Yongsan US Army Garrison (USAG)] and Pyeongtaek (Humphreys USAG) where malaria risks are much lower. Anopheles mosquitoes were identified to species using a multiplex PCR method and then evaluated for the presence of acetylcholinesterase-1 (ace-1) and voltage-gated sodium channel (vgsc) regions to identify mutations linked to insecticide resistance. Analysis of the ace-1 region identified insecticide resistance alleles in four species of the Hyrcanus Group (An. sinensis, An. kleini, An. belenrae, and An. pullus), while ace-1 resistance alleles were not observed in the other four species. The screening of the vgsc gene fragment confirmed the presence of resistant alleles only in An. sinensis (considered a poor malaria vector) and An. kleini (a primary malaria vector) in the ROK. This study represents a preliminary investigation of insecticide resistance mutations across all Anopheles species in the ROK. These findings are crucial in advancing mosquito control strategies to mitigate future malaria infections.